A new off-wall insulation liner for high-speed railway tunnels in cold regions. (December 2021) - Cui, Guangyao; Ma, Jianfei; Wang, Libin; Wang, Xuelai; Wang, Daoyuan
Abstract: This paper has designed a novel off-wall insulation liner, aiming to prevent severe frost damages for the high-speed railway tunnel in cold regions. In terms of composition, the double-layer steel corrugated plates of the liner not only prevent the block falling and water intrusion of cold-region tunnels but prolong the durability and effectiveness of thermal insulation materials. Besides, the quick-construction technology for the off-wall insulation liner was derived in the present study, and it exhibits excellent construction efficiency, great economic and social benefits in the high-speed railway tunnel. Concerning the insulation capacity, the double insulation layers (polyurethane foam and air) perform the dramatical coldness-blocking effect, the freezing line moves forward from 0.48m-deep surrounding rock to the lining surface. The four-year field test has proved the effectiveness and insulation capacity of the off-wall tunnel, the severe frost damages in the Wufengshan tunnel were successfully eliminated. Compared with existing coldproof measures, the off-wall insulation liner in this paper exhibits excellent insulation capacity, high construction efficiency, and excellent economic benefits, it could be applied in the high-speed railway tunnels with high-altitude or extremely low temperatures.